2013
DOI: 10.1016/j.biopsych.2012.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Global Prefrontal and Fronto-Amygdala Dysconnectivity in Bipolar I Disorder with Psychosis History

Abstract: Background Pathophysiological models of bipolar disorder postulate that mood dysregulation arises from fronto-limbic dysfunction, marked by reduced prefrontal cortex (PFC) inhibitory control. This may occur both due to disruptions within PFC networks and abnormal inhibition over subcortical structures involved in emotional processing. However, no study has examined global PFC dysconnectivity in bipolar disorder and tested if regions with within-PFC dysconnectivity also exhibit fronto-limbic connectivity defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
219
3
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(243 citation statements)
references
References 63 publications
15
219
3
6
Order By: Relevance
“…Studies focused on the prefrontal cortex found connectivity in this area to be aberrant using the GBC measure in schizophrenia (Cole et al, 2011;Yang et al, 2014) and bipolar disorder (Anticevic et al, 2013). Others found a reduction in global FC in a group of participants with autistic spectrum disorder in comparison to controls, and, therefore, did not regress the global signal from the data .…”
Section: Gbc Reflects Global Signal Fcmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies focused on the prefrontal cortex found connectivity in this area to be aberrant using the GBC measure in schizophrenia (Cole et al, 2011;Yang et al, 2014) and bipolar disorder (Anticevic et al, 2013). Others found a reduction in global FC in a group of participants with autistic spectrum disorder in comparison to controls, and, therefore, did not regress the global signal from the data .…”
Section: Gbc Reflects Global Signal Fcmentioning
confidence: 99%
“…In addition, the GBC is also used to study clinical populations. For example, specific prefrontal cortex functional alternations in schizophrenia (Cole et al, 2011), bipolar disorder (Anticevic et al, 2013), and obsessive-compulsive disorder (Anticevic et al, 2014) were studied using this method. Recently, this measure was also used to study the relationship between spontaneous FC and schizophrenia-like symptoms in healthy participants (Driesen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, GBCr has been successfully used to identify alterations across major networks in clinical conditions. Reduced PFC GBCr was reported in bipolar, chronic schizophrenia, and obsessive-compulsive disorders; all of which harbor a strong component of chronic stress and were previously related to glutamate synaptic homeostasis (Anticevic et al, 2013;Anticevic et al, 2015a;Anticevic et al, 2014;Cole et al, 2011). Additionally, ketamine has been repeatedly shown to increase PFC GBCr during ketamine infusion in healthy volunteers (Anticevic et al, 2015a;Driesen et al, 2013a;Driesen et al, 2013b).…”
Section: Introductionmentioning
confidence: 96%
“…Acute effects of MDPV at low-to-moderate doses are likely to involve brain reward regions targeted by other stimulants, such as cocaine and METH (Baumann et al, 2012;Simmler et al, 2013), whereas higher doses have the potential to influence other brain networks (Penders and Gestring, 2011). Given the nature of the reported behavioral disturbances, it is possible that MDPV causes disruptions in the coherent interactions among brain regions that are necessary for normal cognition and affect, as reported in other neuropsychiatric conditions involving audiovisual hallucinations (Anticevic et al, 2013;Lui et al, 2009;Sommer et al, 2012;Wolf et al, 2011).…”
Section: Introductionmentioning
confidence: 99%